Etiese vrae oor en perspektiewe op die mediese beeindiging van die lewe - Lategan, Laetus O. K. (Hervormde teologiese studies, 1999)
Ethical questions and perspectives on the medical ending of life. A thorny issue in medical ethics is the medical ending of life. This article looks into the phenomena of abortion and euthanasia as examples of the medical ending of life. For the purposes of this article attention is paid to the theological criteria for abortion and euthanasia. Medical examples are then provided which illustrate the ethical difficulty in dealing with situations in which one has to make a decision whether a life should be medically ended or not The article concludes with pastoral perspectives on dealing with the issues of abortion and euthanasia.